The Role of Nationalism in Shaping Modernity: Towards a Triaxial Theory of National Identity in the Global Digital Era through the Lens of Islamic Education - Suriyadi Suriyadi; Fathorrahman Fathorrahman (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
This study examines the evolving role of nationalism in shaping modernity and proposes a reconstructed Triaxial Theory of National Identity (TTNI) through the lens of Islamic education to address the challenges of the global digital era. The research aims to develop a comprehensive conceptual framework that explains how cultural-historical continuity, civic-democratic values, and digital-network dynamics interact in constructing adaptive national identity while integrating Islamic educational principles. This study employed a qualitative library research approach by systematically reviewing classical and contemporary literature on nationalism, digital society, citizenship education, and Islamic educational philosophy. Data were analyzed using qualitative content analysis, thematic analysis, and comparative conceptual synthesis to identify theoretical convergences, research gaps, and interdisciplinary relationships. The findings reveal that contemporary nationalism can no longer be adequately understood through single-dimensional approaches emphasizing ethnicity, territory, or civic institutions alone. Instead, sustainable national identity emerges from the dynamic interaction among the Cultural-Historical Axis, Civic-Democratic Axis, and Digital-Network Axis, mediated by Islamic educational values such as maqāṣid al-sharī‘ah, ukhuwah waṭaniyyah, wasatiyyah, and ethical digital citizenship. Islamic education plays a strategic role in fostering historical awareness, democratic participation, critical digital literacy, and moral responsibility necessary for strengthening adaptive nationalism in digitally interconnected societies. The novelty of this study lies in reconstructing the Triaxial Theory of National Identity by positioning Islamic education as the ethical and pedagogical mediator that integrates cultural identity, democratic citizenship, and digital literacy into a holistic framework for developing adaptive, inclusive, and ethically grounded nationalism in the era of artificial intelligence and global digital transformation.